Strategi Rumah Moderasi Beragama IAIN Madura dalam Menanamkan Pendidikan Islam Moderat pada Mahasiswa IAIN Madura - M. Nuril Qulub; Moh. Afiful Hair (La-Tahzan: Jurnal Pendidikan Islam, 2025)
The House of Religious Moderation is part of the Indonesian Ministry of Religious Affairs’ initiative to strengthen the values ??of religious moderation within the State Islamic Religious Colleges (PTKIN). IAIN Madura, as one of the PTKINs, has established the House of Religious Moderation since 2019 as a response to the challenges of radicalism and extremism that attack IAIN Madura students. This study examines in depth the strategy of the House of Religious Moderation in instilling moderate Islamic education in IAIN Madura students. This study uses qualitative research with the type of field research. The research location is at IAIN Madura. Data collection techniques use interviews, observation, and documentation. The results of the study indicate that the strategies of the House of Religious Moderation at IAIN Madura include: 1) through education, through research, through training, through social media. 2) this strategy is considered quite effective in shaping an understanding of moderate Islam for students by strengthening moderation cadres, socializing diverse religious moderation, and collaboration between IAIN Madura academics. 3) Obstacles include students’ lack of understanding of religious moderation, fanaticism toward Islamic organizations, and digital influence. Solutions include implementing ongoing religious moderation training for students, creating creative content to convey the message of moderate Islam, and exemplary behavior by lecturers and religious moderation ambassadors.